2014
DOI: 10.1016/j.jjcc.2014.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of elevated neutrophil to lymphocyte ratio for long-term cardiovascular mortality in peripheral arterial occlusive disease

Abstract: We demonstrated that an increased NLR was related with higher cardiovascular mortality in patients with PAOD, who were admitted with critical limb ischemia or intermittent claudication. NLR, which reflects the patient's inflammatory status, is an inexpensive and readily available biomarker that provides an additional level of risk stratification beyond that provided by conventional risk scores in predicting long-term cardiovascular mortality in PAOD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
3
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 33 publications
4
55
3
4
Order By: Relevance
“…In medical inpatients with multiple chronic conditions, increased NLR was associated with mortality [21]. In patients with peripheral arterial occlusive disease, increased NLR was related with higher cardiovascular mortality [22]. Okyay et al [23] noted that laboratory measurement of NLR, which is relatively easy and inexpensive, might provide significant information regarding inflammation in CKD, including in predialysis and dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In medical inpatients with multiple chronic conditions, increased NLR was associated with mortality [21]. In patients with peripheral arterial occlusive disease, increased NLR was related with higher cardiovascular mortality [22]. Okyay et al [23] noted that laboratory measurement of NLR, which is relatively easy and inexpensive, might provide significant information regarding inflammation in CKD, including in predialysis and dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the cutoff value for NLR was set as 2.81 based on the ROC value used in the cardiac study performed in our hospital [11]; in other studies, it has been reported as 2.72 and 3 [34,35]. NLR has been considered as a good marker in the prediction of the outcomes in cardiac diseases [31][32][33][34][35][36]. Similarly, high NLR value was found to be an independent predictor of CAE development based on both univariate and multivariate analyses.…”
Section: Neutrophil-to-lymphocyte Ratio (Nlr)mentioning
confidence: 99%
“…5,6 Unlike TNF-alpha and IL-6, which require separate tests, NLR can be readily calculated from a patient's full blood count without incurring additional cost. NLR has been identified as a marker of systemic inflammation and prognostic marker for mortality in patients with solid organ malignancies, 7 peripheral vascular disease, 8,9 and in the setting of acute coronary syndrome. 10,11 Despite this, few studies have investigated the prognostic value of NLR in patients with chronic kidney disease, with none focusing solely on hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%